2014
DOI: 10.1681/asn.2013040361
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between Novel Oral Anticoagulants and Vitamin K Antagonists in Patients with CKD

Abstract: Novel oral anticoagulants (NOACs) (rivaroxaban, dabigatran, apixaban) have been approved by international regulatory agencies to treat atrial fibrillation and venous thromboembolism in patients with kidney dysfunction. However, altered metabolism of these drugs in the setting of impaired kidney function may subject patients with CKD to alterations in their efficacy and a higher risk of bleeding. This article examined the efficacy and safety of the NOACs versus vitamin K antagonists (VKAs) for atrial fibrillati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 40 publications
1
54
1
1
Order By: Relevance
“…[165][166][167][168][169] A recent systematic review did not find that the newer agents were superior, but the point estimate for the risk of stroke was compatible with a substantial clinical benefit compared with warfarin despite a similar risk of bleeding ( Figure 5). 170,171 Additional trials are ongoing, and more information will soon be available.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…[165][166][167][168][169] A recent systematic review did not find that the newer agents were superior, but the point estimate for the risk of stroke was compatible with a substantial clinical benefit compared with warfarin despite a similar risk of bleeding ( Figure 5). 170,171 Additional trials are ongoing, and more information will soon be available.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…The risk of major bleeding or the combined endpoint of major bleeding or clinically relevant non-major bleeding was similar between the groups. 41 A population-based nested case-control study in older patients with moderate CKD not on dialysis showed an increased risk for hemorrhage and that exposure to dabigatran or rivaroxaban was not associated with a statistically significant increased risk of major hemorrhagic events as compared to warfarin. 42 A limitation of the study was that only an algorithm was used to detect patients with CKD with missing individual GFR estimations.…”
Section: Direct Oral Anticoagulantsmentioning
confidence: 99%
“…A subgroup analysis of patients with moderate renal impairment (CrCl 30-50 mL/min) indicated that when dosed according to the manufacturers' recommendations, DOACs are at least as safe as warfarin. 16,17 Dose adjustments are also warranted based on indication, age, and weight and can be further complicated by the addition of interacting drugs. Additionally, not all DOACs are approved for the same indications as VKAs.…”
mentioning
confidence: 99%